Women and the Archives : The Search for Images of Filipinas in Colonial Photography - Jose, Mary Dorothy (Philippine Journal of Librarianship and Information Studies, 2022)
This paper argues that finding women in the archives can be manageable if one is equipped with the appropriate methodology and feminist perspective. Archives can be considered as important repositories of sources on women waiting to be explored, with historical and photographic records shedding light on how women are represented in various historical periods. For this study, three collections from the University of Michigan archives yield interesting data on how Filipino women were represented in American colonial photography.